Financial Literacy and Financial Management Behavior: Mediating Effects of Financial Self Efficacy and Family Financial Socialization in Food and Beverage MSMEs - Sinaga, Junitri; Dewi Djunaedi, Mira Kartika (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Poor money handling still creates problems for micro, small, and medium enterprises (MSMEs), particularly in the food and drink sector. Issues like low financial literacy (FL), insufficient financial self-efficacy (FSE), and the effect of family financial socialization (FFS) are thought to change how business owners manage their finances (FMB). This study aims to look at how FL affects FMB, while also considering the parts played by FSE and FFS as connecting factors among MSME owners in the food and drink area of DKI Jakarta. A measurement approach is used, using a questionnaire method, with information being processed using Structural Equation Modelling–Partial Least Squares. Discoveries show that FL has a good effect on FMB, FSE, and FFS. Furthermore, both FSE and FFS are proven to have a helpful impact on FMB and act as connectors between FL and FMB. These outcomes indicate that the FMB of MSMEs is affected not only by how much financial understanding the owners have, but also by both mental and group factors that impact how financial understanding is put into practice in actual situations. This paper provides a conceptual benefit that deepens the grasp of MSME money actions and offers a useful benefit that can guide the making of fuller and longer lasting rules and plans for MSME expansion.